Toward Continuous Primary Care in the United States - Ala I. Iaconi MS; Jongwha Chang MA, MS; Steve Feldman MD, PhD; Rajesh Balkrishnan PhD (SAGE Publishing, 2011)
Background : As stated by Donabedian, the father of quality assurance, satisfaction is an integral component of quality in medical care. Patient satisfaction is an important predictor of health-related behaviors, use of medical services, and health outcomes. Impressive literature exists in examining various aspects of patient satisfaction, however, no study thus far has examined differences in patient satisfaction between first and return visits to primary care physicians. Objective : Our interest is to determine whether there are differences in patient satisfaction between first and return visits to primary care physicians, with the hypothesis that patients returning for their visits have a higher satisfaction level compared to their first initial visit. Methods : The authors conducted a cross-sectional analysis of the national Web-based survey DrScore. Via DrScore, patients anonymously rated their physician on the basis of treatment satisfaction received from their most recent outpatient visit. The association between physician satisfaction and total care patient ratings of first and return visits was assessed via regression analysis. Results : In total, 15,341 patients were included in this study. Our findings indicate that for a 1-unit change from first visit to return visits, the coefficient of patient satisfaction for the return visits is approximately 10 times higher compared to that of the first visit. Furthermore, the mean satisfaction score for the return visit group is higher than that for the first visit group, 80.28 versus 64.48, respectively ( P < .05). Conclusion : Return visits to primary care physicians are associated with higher patient satisfaction compared to the first initial visit.